Determinants of internal migration in Norway - David McArthur; Inge Thorsen (European Regional Science Association (ERSA), 2010)
This paper uses panel data on migration flows between municipalities in Norway from 2000-2008. The relatively new method of fixed effects vector decomposition (fevd) is used to estimate parameters for time-invariant spatial structure variables as well as for labour market factors such as unemployment rates, income and house prices. We compare several model specifications. Results on employment/unemployment are fairly consistent across models. Results on other variables, for instance income and house prices, are less robust. We also experiment with several measures of spatial structure, which adds considerably to the explanatory power of the model, as expected.
Keywords: J61; R23; 330; Internal migration; fixed effects vector decomposition; spatial structure; unemployment